Computer languages - Lampton, Christopher. 4 0 16; Berger, Melvin; 5 (New York : F. Watts, 1983)
Introduces computer programming languages including FORTRAN, COBOL, BASIC, PASCAL, and LOGO.
Includes index.
Booklist;Reference and Research Book News
7.7;5-8;5-8
Keywords: 2 -- 0; 6; Programming languages (Electronic computers).;Computers.;Programming languages (Electronic computers).; 20; 2